Avaliação de estratégias para desenvolver habilidades comunicativas verbais em indivíduos com autismo de alto funcionamento e síndrome de Asperger. - Lopes-Herrera, Simone Aparecida (2004)
The high-functioning autism and Asperger syndrome are pervasive developmental disorders, that among other simptoms, present in higher or lower level alteration in communicative and social abilities. This study was developed according the verbal communicative abilities of autism and Asperger syndrome described by Lopes (2000), and is divided in two parts with the following objectives: (a) for part 1 the objective was to realize a survey of strategies, activities and communicative contexts that could support the use of a higher number of verbal communicative abilities and, consequently, a major mean length utterance, talk complexity or major use of narrative discursive abilities expressed by individuals with high-functioning autism and Asperger syndrome in their verbal interactions with the adult interlocutor; (b) For part 2 of the study, the objective was the application of strategies surveyed in part 1 of the study in its original or adapted format with three 12 year old male (one diagnosed as having Asperger syndrome and the other 2 diagnosed as high-functioning autism) in order to increase their mean length utterance, by using the verbal communicative abilities as well as to verify if the increase of the mean length utterance would benefit the use of narrative discursive abilities. The data was collected from Lopes (2000), Master Thesis, during individuals interaction sessions with the researcher. By that time, the participants were 8 years old. Five sessions tapes of each participant were evaluated, with a total of 450 minutes. The results of part 1 of the study demonstrated that there is a communicative reciprocity between the adult and the participants and that their communicative profile are similar, since the values of the mean length utterance (MLU) and talk complexity (TC) demonstrated by the adults were higher, but it was possible to note that the variation continues the same for example - when the adult scored a higher MLU with one of the participants, it was exactly that participant that scored a higher MLU in relation to the others. According to these fidings, the part 1 of the study enabled to survey the activities, strategies, facilitating contextualized situations and, consequently, to organize an intervention program (with structured sessions) that was applied and evaluated in part 2 of the study. In this second part of the study, all verbal interaction structured sessions with each participant and researcher were videotaped. In order to verify the effects of the application of the strategies, a single subject research design across subject was used, and envolved two phases: baseline and intervention. During baseline, spontaneous situations ocurred between the adult and each participant. The participants were not submited to any kind of intervention. After the baseline stability, the first phase of the intervention was initiated (sessions were twice a week). The second phase (sessions once a week) was initiated only when the participant reached performance 100% higher in mean length utterance than the one reached in basleline. The number of sessions were gradually decreased for each participant in order to assure their performance. However, the number of sessions varied from one participant to another. The applied strategies were divided in blocks: spontaneous conversation, specific language dificulties, games with rules, estory report and metalinguistic activities. The results of part 2 of the study demonstrated that the aplication of the proposed strategies with the three participants reached the objective to increase their mean length utterance. In consequence, participant s use of narrative discursive abilities were also increased. Suggestion for further research are made in terms of maintenance of the obtained results with individuals with Asperger syndrome and high-functioning autism in other environments and in interaction with other interlocutors.